5(2x-10)=

Simple and best practice solution for 5(2x-10)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x-10)= equation:


Simplifying
5(2x + -10) = 0

Reorder the terms:
5(-10 + 2x) = 0
(-10 * 5 + 2x * 5) = 0
(-50 + 10x) = 0

Solving
-50 + 10x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '50' to each side of the equation.
-50 + 50 + 10x = 0 + 50

Combine like terms: -50 + 50 = 0
0 + 10x = 0 + 50
10x = 0 + 50

Combine like terms: 0 + 50 = 50
10x = 50

Divide each side by '10'.
x = 5

Simplifying
x = 5

See similar equations:

| 15(v+2)-3v=3(4v+3)-14 | | (1/x^2)=95 | | 20x^3-1=0 | | (x+6)(8x-1)=0 | | 23=23/x | | 5-d=-11 | | 225=-8x-7(1+3x) | | 23/x=23 | | 5k^2+17k-20=-8 | | 2(c-9)=4 | | 7K=-91 | | 3y-2y=16 | | -x+16=3x+4 | | 5x^4-x=0 | | 3=z-4/2 | | 170-(160-x)+x=180 | | 2[2(6x+3)-5(2x-4)]= | | 3(x-3)-x=5 | | 6x+1=4x-30 | | 7=p*4+8 | | -2(c+18)=-8 | | 5x-23=56 | | X+8+6x=-69 | | -x+23=x+7 | | d/dx(f(3x^2)) | | -6x-12=4(2x-3) | | (x^4)^-1/4 | | 4u=u+48 | | 26-4x=7x-29 | | 84=6(n+8) | | 123/324 | | 84=6(n-8) |

Equations solver categories